Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1093/humrep/12.11.2443
|View full text |Cite
|
Sign up to set email alerts
|

Results of percutaneous epididymal sperm aspiration and intracytoplasmic sperm injection in two major groups of patients with obstructive azoospermia

Abstract: Percutaneous epididymal sperm aspiration (PESA) and intracytoplasmic sperm injection (ICSI) were carried out in patients with congenital bilateral absence of the vas deferens (CBAVD) and men with failed reversal of vasectomy (FRV). PESA was successful in 55 out of 62 patients with CBAVD (89%) and in 57 out of 60 men with FRV (95%). The fertilization rates after ICSI (53 and 55%), cleavage rates (70 and 76%) and pregnancy rates (36 and 32%) did not differ significantly between the two respective groups (CBAVD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
4
11
0
Order By: Relevance
“…The only study that reported implantation rate [13] showed similar findings (19% and 16%) to the present 15.8% for congenital and 15.0% for acquired OA, respectively, with no difference between the groups.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The only study that reported implantation rate [13] showed similar findings (19% and 16%) to the present 15.8% for congenital and 15.0% for acquired OA, respectively, with no difference between the groups.…”
Section: Discussionsupporting
confidence: 82%
“…Mansour et al [10] reported similar FRs in the two groups (56.6% vs 55.2%) but a significantly higher pregnancy rate in the acquired OA group (37% vs 20.4% per transfer). Meniru et al [13] used PESA as their preferred method of retrieval in 1997, and found no difference in outcome between the groups. More recently, a further large series with over 100 cycles (all MESA) in each group showed similar FR, pregnancy/cycle and delivery/cycle rates between the congenital and acquired groups (73.1%, 61.6% and 53.6% vs 72.4%, 48.5% and 46.6%, respectively [11]).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors are confirming the efficiency of PESA (3,7,10). Our results have shown that the chance of obtaining motile spermatozoa in a first PESA procedure was 81%, thus confirming the efficiency of this procedure.…”
Section: Discussionsupporting
confidence: 85%
“…[89] However, there are some reports showing enough evidence for their compatibility of fertilization. [1011] In spite of normal spermatogenesis, sperms could not be ejaculated into the semen due to either obstruction in the ejaculatory ducts or a congenital absence of the vas deferens. In this study, the sperms obtained from the epididymis were used for IVF and for ICSI.…”
Section: Discussionmentioning
confidence: 99%